Gambaran Perilaku Remaja Putri Dalam Mengkonsumsi tablet tambah darah di SMA NU Gresik dan MAN X Sidoarjo Tahun 2024 - Ainin, Ainin Zain Zahro; Cicik Swi Antika; Fitrah Bintan Harisma; Bambang Hariyono (Sekolah Tinggi Ilmu Kesehatan Madani Yogyakarta, 2025)
Anemia remains a significant health challenge for adolescent girls in Indonesia. Although a nationwide blood supplementation program has been implemented, the compliance rate of blood supplement consumption is still low. This study aimed to describe the behavior of adolescent girls in consuming TTD at SMA NU Gresik and MAN Sidoarjo, and identify supporting and inhibiting factors, including the role of schools and health center. This study used a qualitative approach with interviews, questionnaires, and Focus Group Discussion (FGD) methods. The results showed that differences in school policies, inaccurate understanding, negative perceptions, and unhealthy lifestyles were the main factors for low TTD consumption compliance. An attractive and consistent educational approach, as well as collaboration between schools, health centers, and parents are needed to increase awareness and compliance of adolescent girls in consuming TTD regularly.